Efficacy of moxibustion in diarrhea-predominant irritable bowel syndrome model rats: a systematic review and meta-analysis - Rao, Xiang; Xing, Yu; Ji, Changchun; Guo, Jixing; Li, Hong-Bao; Xie, Chaoju; Bai, Juan; Wang, Xuejiao; Li, Ying; Zhao, Jingyu (Frontiers in Bioengineering and Biotechnology, 2023)
To systematically evaluate the efficacy of moxibustion in diarrhea-predominant irritable bowel syndrome (IBS-D) model rats.A comprehensive search was conducted in the China National Knowledge Infrastructure, WanFang Data, VIP, PubMed, Embase, and Web of Science databases from their inception to June 30, 2023. Relevant animal experiments investigating moxibustion for treating IBS-D in model rats were included. Two independent researchers screened the literature, extracted data, and evaluated the risk of bias in the selected studies. The meta-analysis was performed using RevMan 5.3 software.In total, 21 animal studies comprising 680 model rats were included. The meta-analysis results demonstrated that moxibustion enhanced the threshold capacity of the abdominal withdrawal reflex (AWR) (standardized mean difference [SMD] = 1.84; 95% confidence interval [CI]: 1.09, 2.60; P <0.00001), ameliorated the rate of loose stool (SMD = -4.